A Place for Healing the Earth and the Body - Alberto Pérez-Goméz (Oz, 1994)
Architecture today seems to be caught in either irrelevant formal games whose seductive power is invariably inferior to the media, or latantly affirming the strong, repressive values of technology and political/commercial publicity. My teaching and theoretical work over the years has been concerned wirh examining the possibilities of an architecture capable of establishing a framework for effective social order and meaning, without resorting to nostalgic formulations or dangerous reductions.